Site-specific serine phosphorylation of spinach leaf sucrose-phosphate synthase. - Huber, J L (1992)
We recently reported [Huber, Huber & Nielsen (1989) Arch. Biochem. Biophys. 270, 681-690] that spinach (Spinacia oleracea L.) sucrose-phosphate synthase (SPS; EC 2.4.1.14) was phosphorylated in vivo when leaves were fed [32P]Pi. In vitro the enzyme was phosphorylated and inactivated by using [gamma-32P]ATP. We now report that SPS is phosphorylated both in vivo and in vitro on serine residues. The protein is phosphorylated at multiple sites both in vivo and in vitro as indicated by two-dimensional peptide maps of the immunopurified SPS protein. After being fed with radiolabel, leaves were illuminated or given mannose (which activates the enzyme), in the presence or absence of okadaic acid. Feeding okadaic acid to leaves decreased the SPS activation state in the dark and light and in leaves fed mannose. Across all the treatments, the activation state of SPS in situ was inversely related to the labelling of two phosphopeptides (designated phosphopeptides 5 and 7). These two phosphopeptides are phosphorylated when SPS is inactivated in vitro with [gamma-32P]ATP, and thus are designated as regulatory (inhibitory) sites [Huber & Huber (1991) Biochim. Biophys. Acta 1091, 393-400]. Okadaic acid increased the total 32P-labelling of SPS and in particular increased labelling of the two regulatory sites, which explains the decline in activation state. In the presence of okadaic acid, two cryptic phosphorylation sites became labelled in vivo that were not apparent in the absence of the inhibitor. Overall, the results suggest that light/dark regulation of SPS activity occurs as a result of regulatory serine phosphorylation. Multiple sites are phosphorylated in vivo, but two sites in particular appear to regulate activity and dephosphorylation of these sites in vivo is sensitive to okadaic acid.